Heat Transfer Enhancement in a 4-Holed Cored Brick Regenerator by Inducing Turbulence - Ramakrishnan, P.; Krishnan, A. S. (Asian Review of Mechanical Engineering, 2017)
The article reports on the transient heat transfer and fluid flow in the sensible heat storage device using Computational Fluid Dynamics. The geometry considered is a cylinder of 455mm length and 43mm diameter made up of mild steel material. Numerical investigations have been done for a porosity of 0.4 and inlet velocity of 2m/s which corresponds to mass flow rate of 0.0035 kg/s by use of commercial CFD software. In CFD software the three dimensional geometrical model of the cored brick heater was modelled, meshed and simulated for 4 holed cored brick which corresponds to the hole size of 13.6mm. The fluid flow was considered to be incompressible with k-ε model to predict turbulence, and the thermo-physical properties of fluid and solid were assumed to remain constant. Thermal performance of storage system such as charging and discharging time were evaluated. A parametric study was conducted for different thermal conductivity, to simulate axial temperature variation and pressure drop across the system. Temperature simulations are carried out by input as 465K as the condition in the regenerator. The lateral and outlet condition of the regenerator are given as adiabatic and atmospheric condition. This paper represents the fluid flow across the 4 hole cored brick with and without inducer, where the inducer induces the laminar flow to turbulent. Thus the fluid flows is at low Renoylds number in the laminar regime and due to the presence of the inducer the flow get transformed to higher Renoylds number in the turbulent regime. Analysis is made for without inducer, inducer at the entrance of each holes and inducer is just next to the developing length on each holes. Result of the computational analysis was made for cases with and without the presence of inducer.